Genetic Mapping of a Light-Dependent Lesion Mimic Mutant Reveals the Function of Coproporphyrinogen III Oxidase Homolog in Soybean - Ma, Jingjing; Yang, Suxin; Wang, Dongmei; Tang, Kuanqiang; Feng, Xing Xing; Feng, Xian Zhong (Frontiers in Plant Science, 2020)
Lesion mimic mutants provide ideal genetic materials for elucidating the molecular mechanism of cell death and disease resistance. Here, we isolated a Glycine max lesion mimic mutant 2-1 (Gmlmm2-1), which displayed a light-dependent cell death phenotype. Map-based cloning revealed that GmLMM2 encods a coproporphyrinogen III oxidase and participates in tetrapyrrole biosynthesis. Knockout of GmLMM2 led to necrotic spots on developing leaves of CRISPR/Cas9 induced mutants. The GmLMM2 defect decreased the chlorophyll content by disrupting tetrapyrrole biosynthesis and enhanced resistance to Phytophthora sojae. These results suggested that GmLMM2 gene played an important role in the biosynthesis of tetrapyrrole and light-dependent defense in soybeans.